Graphene and Carbon Nanotubes Fibrous Composite Decorated with PdMg Alloy Nanoparticles with Enhanced Absorption–Desorption Kinetics for Hydrogen Storage Application - Bassim Arkook (MDPI AG, 2021)
We describe a graphene and fibrous multiwall carbon nanotubes (f-MWCNT) composite film prepared by plasma-enhanced chemical vapor deposition for use as a suitable and possible candidate of hydrogen storage materials. A high storage capacity of 5.53 wt% has been obtained with improved kinetics. The addition of binary PdMg alloy nanoparticles to the surface of graphene-fibrous nanotubes composite films raised the storage capacity by 53% compared to the film without PdMg decorated nanoparticles. Additionally, the graphene/f-MWCNT composite film decorated with PdMg nanoparticles exhibited an enhanced hydrogen absorption–desorption kinetics. The fibrous structure of the MWCNTs, alongside graphene sheets within the film, creates an enormous active region site for hydrogen reaction. The addition of PdMg nanoparticles enhanced the reaction kinetics due to the catalytic nature of Pd, and increased the hydrogen content due to the high absorption capacity of Mg nanoparticles. The combination of Pd and Mg in a binary alloy nanoparticle enhanced the hydrogen capacity and absorption–desorption kinetics.